Corporate real estate enterprise risk management framework of business organisations / Noraliza Basrah - Basrah, Noraliza (Institute of Graduate Studies, UiTM, 2016)
Enterprise risk management (ERM) has been recognized as the best practice for risk management worldwide. It is an integrated approach that manages all significant risks of the business organisations. This research study explores the possibility to enhance the ERM concept into protecting the organisational business continuity using the principles of corporate real estate management. It aims to establish the corporate real estate enterprise risk management framework (CREERM) that incorporates the corporate real estate strategies as a specialized tool for strategic risk management in organisations. The research objectives are to identify the encompassing elements of risk management and ERM in theory and practice, to develop and test the CREERM conceptual framework and finally, to refine and validate the proposed CREERM framework. The research strategy begins with the review and observations of the established risk management frameworks in theory and published research as well as the ones in business practice. This involves the quantitative and qualitative content analysis of the academic literature and the Malaysian Top 100 company (by market capitalisation as at 28th June 2010) annual reports through a scoping study to determine the organisations’ risk management capabilities. Results showed that regardless of the organisations’ core business, among the key factors determining their rank position are the risk management skilled personnel and their risk management experience. The top three risk management capabilities that fall within the advanced level of maturity among these organisations are risk awareness and communication, risk management establishment and training for staff. Critically overlooked elements are their RM system, risk profile, BCM and RM strategies…